SNAKE LADDER GAME MODIFIED BASED ON IT WITH TEAM GAME TOURNAMENT MODEL ON LEARNING IPA - Winastiti, R. N.; Widihastrini, F.; Hartati, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
Based on the pre-research activity done, learning condition at fourth grade of SDN Gisikdrono 03 were not using learning media in science subject. Thus the action is needed to improve the science learning quality by developing ladder snake game-IT based on science learning with TGT model at SDN Gisikdrono 03. The purpose of this research was to improve the students activity and students learning outcome. The design of this research is research and development study (R & D). The subjects of the research are the fourth gradersat SDN Gisikdrono 03. Expert assessment results indicate that ladder snake game-IT based deserves for test material, media and language of experts. The percentage of the component assessment of content eligibility was 94.64% (very feasible), the component assessment of the media representation was 80% (very feasible), and the component assessment of literary was 75% (feasible). The result also showed that ladder snake game-It based affects cognitive learning results proven by the presence of difference in average studentsâunderstanding through T-test was 2.007 andÂ average increase (gain) was 0.586 (fair). Studentsâ activity got score of 84.49% (very good). The study can be concluded that ladder snake game-IT based on science subject with TGT model can improve students learning outcome and students activity on material in the form of energy.